Spiritual Therapy for Patients and Communities Reducing Anxiety during the COVID-19 Pandemic: A Literature Review - Dimas Utomo Hanggoro Putro; Siti Nurjanah; Christantie Effendy (Journal Of Nursing Practice, 2025)
Background: COVID-19 poses high challenges for society and has a considerable impact. One of the impacts of COVID-19 on patients and society is the emergence of anxiety, so efforts are needed to reduce this anxiety. Spiritual therapy is an alternative that can be used by patients and communities affected by COVID-19. Purpose: Find specifically about spiritual therapy to reduce anxiety in COVID-19 patients and communities affected by the COVID-19 pandemic. Methods: Literature review of international literature using Google Scholar, Proquest, and Taylor & Francis databases. A total of 1,544 articles were identified, of which 995 were duplicates, leaving 549 articles. After screening, 539 articles were excluded due to the lack of full-text availability. The remaining 10 articles were further reviewed, resulting in 5 articles that met the criteria and were included in this study. Results: Five articles meeting the inclusion criteria. One true experiment article, 2 pre-experiment articles, 1 RCT article, and 1 qualitative article. All articles analyzed are articles published in the range of 2019-2021. Spiritual therapies that can be used to reduce anxiety include Spiritual Emotional Freedom Technique (SEFT), Benson therapy, psychoreligious therapy, mindfulness meditation, and spiritual psychotherapy with an Islamic religious education approach. Conclusion: COVID-19 has profoundly impacted daily life and created significant challenges for society. However, spirituality serves as an important coping resource to help individuals manage anxiety. Various spiritual therapies such as the SEFT, benson relaxation, psychoreligious therapy, mindfulness meditation, and spiritual psychotherapy based on Islamic teachings have been shown to effectively reduce anxiety and promote mental well-being during the pandemic.